2021
DOI: 10.1136/bmjgh-2020-004080
|View full text |Cite
|
Sign up to set email alerts
|

Development of measures for assessing mistreatment of women during facility-based childbirth based on labour observations

Abstract: IntroductionMistreatment of women during childbirth is increasingly recognised as a significant issue globally. Research and programmatic efforts targeting this phenomenon have been limited by a lack of validated measurement tools. This study aimed to develop a set of concise, valid and reliable multidimensional measures for mistreatment using labour observations applicable across multiple settings.MethodsData from continuous labour observations of 1974 women in Nigeria (n=407), Ghana (n=912) and Guinea (n=655… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…While measuring mistreatment using either a community survey or labour observation depends on resources available, we also note that any research or monitoring related to women’s experiences of care should allow women to report on what matters most to them. Shortened and full versions of the tools used in our analyses can inform key areas of focus, while cognisant of certain types of mistreatment that may be feasible to rule out but difficult to detect with observation and might need to be explored further using two methods 32 33. Furthermore, the measurement approaches need to be interpreted in the context of tool implementation for effective action on improving quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While measuring mistreatment using either a community survey or labour observation depends on resources available, we also note that any research or monitoring related to women’s experiences of care should allow women to report on what matters most to them. Shortened and full versions of the tools used in our analyses can inform key areas of focus, while cognisant of certain types of mistreatment that may be feasible to rule out but difficult to detect with observation and might need to be explored further using two methods 32 33. Furthermore, the measurement approaches need to be interpreted in the context of tool implementation for effective action on improving quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis has both strengths and limitations. This study builds on the strengths of the WHO ‘How women are treated during facility-based childbirth’ study, which developed tools specifically to capture mistreatment that have been validated in four countries 32 33. The robust approach to the analysis allowed us to consider individual-level and population-level accuracy of labour observations relative to the community survey.…”
Section: Discussionmentioning
confidence: 99%
“…50 51 The analysis of labour observations from the same study found evidence for cross-country comparability in items and scores for a scale on interpersonal abuse and item sets for exams and procedures and unsupportive birth environment, potentially reflecting the comparability of trained observers applying prestandardised definitions to the widely varying experience of childbirth. 27 Woman-centred measures of quality of care and birth experiences are critical to evaluating maternity care, as women are the best experts on their own experiences, 9 but such assessments must consider the power imbalance that contributes to mistreatment and may shape the perception and reporting of it. 7 As a priority for future research, triangulation between the observations of care and women's self-reports will help to identify what types of mistreatment can be monitored with greater sensitivity using direct observation, particularly for marginalised women.…”
Section: Discussionmentioning
confidence: 99%
“…11 Secondary analysis of the direct observation data from Ghana, Guinea and Nigeria identified consistent measures across these countries for interpersonal abuse, exams and procedures, and unsupportive birth environment. 27 Further use of the community survey tool will be informed by a similar understanding of whether items function as scales to provide domain scores and if subsets of items can provide comparable insight to the original comprehensive item list.…”
Section: Key Questionsmentioning
confidence: 99%
“…The Berger and Leslie papers used the full versions of the validated WHO tools for observation and community survey and developed shorter versions for easy use. Berger tested a set of three concise measures of mistreatment for facilities that ‘can be adapted and used in future research and quality improvement initiatives to quantify the burden, frequency and overlap of multiple types of mistreatment in a standardised way that can be compared across studies, settings and time periods’ 15 16. These papers advance our understanding of measurement issues of mistreatment and provide new knowledge of methodologies and scales that can be used and adapted by programmes in many countries.…”
Section: Filling Gaps In Evidence For Respectful Maternity Carementioning
confidence: 99%